2012
DOI: 10.1107/s0108768112042826
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and database-transferred electron-density analysis and evaluation of electrostatic forces in coumarin-102 dye

Abstract: The electron-density distribution of a new crystal form of coumarin-102, a laser dye, has been investigated using the Hansen-Coppens multipolar atom model. The charge density was refined versus high-resolution X-ray diffraction data collected at 100 K and was also constructed by transferring the charge density from the Experimental Library of Multipolar Atom Model (ELMAM2). The topology of the refined charge density has been analysed within the Bader `Atoms In Molecules' theory framework. Deformation electron-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…These molecules have large aromatics parts research papers IUCrJ (2014). 1, 119-128 Christian Jelsch et al Enrichment ratio of atomic contacts 121 Table 1 Example of Hirshfeld contact surfaces and derived 'random contact' and 'enrichment ratios' for the coumarin-102 crystal (Bibila Mayaya Bisseyou et al, 2012).…”
Section: Ch Aromatic Compoundsmentioning
confidence: 99%
“…These molecules have large aromatics parts research papers IUCrJ (2014). 1, 119-128 Christian Jelsch et al Enrichment ratio of atomic contacts 121 Table 1 Example of Hirshfeld contact surfaces and derived 'random contact' and 'enrichment ratios' for the coumarin-102 crystal (Bibila Mayaya Bisseyou et al, 2012).…”
Section: Ch Aromatic Compoundsmentioning
confidence: 99%
“…The relative stability of the closed-shell d 10 Cu­(I) system compared to that of the d 9 Cu­(II) system is likely to make the cleavage of the Cu–N bond favorable. Further CM5 (Bader) charge analysis also revealed that upon H atom addition, the charge on the Cu centers decreases from 0.70(0.98) e – to 0.53(0.70) e – , consistent with the reduction of Cu­(II) to Cu­(I). On the other hand, the CM5 and Bader charges on the Ni centers remain unchanged (Table S8) for all of the structures, suggesting no change in the formal oxidation states of the Ni centers.…”
Section: Results and Discussionmentioning
confidence: 84%
“…Therefore, we employed the electron transfer-based MoPro-ELMAM2 model to gain insights into the electron density, strength, and nature of short contacts . Furthermore, several studies , have confirmed that both multipole refinement and MoPro-ELMAM2 models exhibit a consistent trend in the topological values at the BCPs and demonstrate excellent quantitative and qualitative agreement. In this study, our primary focus lies in investigating hydrogen bonding interactions involving the H···O and H···Cl – contacts.…”
Section: Resultsmentioning
confidence: 91%